2000
DOI: 10.1097/00001756-200002070-00001
|View full text |Cite
|
Sign up to set email alerts
|

Noise affects auditory and linguistic processing differently

Abstract: We investigated the influence of noise on brain responses to spoken sentences in MEG. Sixteen subjects had to listen to acoustically presented sentences and judge their syntactic correctness. Sentences were either presented on a silent background or with noise. Noise had differential effects on early auditory and syntactic processes. While noise affected early auditory processes only in the right hemisphere, noise had a general effect on syntactical processes. The evoked responses to syntactic violations compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 6 publications
3
24
1
1
Order By: Relevance
“…An MEG study on sentence perception reported that noise presented with 75 dB sound intensity disrupted early auditory processing only in the right hemisphere [Herrmann et al, 2000]. Our results underline these findings in that we noticed stronger functional activation in the right relative to the left mid portion of the auditory cortex for the ''silent'' as opposed to the ''noisy'' fMRI.…”
Section: Discussionsupporting
confidence: 81%
“…An MEG study on sentence perception reported that noise presented with 75 dB sound intensity disrupted early auditory processing only in the right hemisphere [Herrmann et al, 2000]. Our results underline these findings in that we noticed stronger functional activation in the right relative to the left mid portion of the auditory cortex for the ''silent'' as opposed to the ''noisy'' fMRI.…”
Section: Discussionsupporting
confidence: 81%
“…To compare the previous MEG experiment ( Herrmann et al, 2000) without pitch flattening with the present data, we re-analyzed the previous data. We reduced the original number of subjects ðn ¼ 16Þ to match the present investigation ðn ¼ 11Þ keeping those subjects which participated in both experiments ðn ¼ 5Þ.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies on central auditory processing used only one type of background noise, not comparing the effects of different noise types on speech processing (Shtyrov et al, 1998;Martin et al, 1999;Herrmann et al, 2000;Salvi et al, 2002). The issue of noise effects beyond the peripheral auditory mechanism has been raised by the observation that various background conditions have different effects on speech recognition performance compared to silent conditions.…”
Section: Introductionmentioning
confidence: 99%